A cascade-reaction enabled synergistic cancer starvation/ROS-mediated/chemo-therapy with an enzyme modified Fe-based MOF. (30th July 2019) - Liu, Zongjun; Li, Tuo; Han, Fang; Wang, You; Gan, Yang; Shi, Junhui; Wang, Tianran; Akhtar, Muhammad Luqman; Li, Yu
Abstract : A cascade-reaction enabled synergistic starvation/ROS-mediated/chemo-therapy was developed, and it exhibits a remarkable therapeutic efficacy without any external intervention. Abstract : Synergistic cancer starvation/ROS-mediated/chemo-therapy is developed through a cascade reaction with enzyme glucose oxidase (GOX) modified on the surface of an Fe-based metal organic framework (MOF(Fe)) and drug camptothecin (CPT) loaded into the cavities of MOF(Fe). Once internalized by tumor cells, GOX catalyzes endogenous glucose into hydrogen peroxide (H2 O2 ) and gluconic acid (H + ) enabling starvation therapy through choking off energy (glucose) supply. Meanwhile, the acidic micro-environment of tumor enhanced by the generated H + degrades the MOF(Fe) simultaneously releasing CPT for chemotherapy and Fe 3+, catalyzing H2 O2 into one of the strongest reactive oxygen species (ROS) ˙OH enabling ROS-mediated therapy. Both in vitro and in vivo results show remarkable tri-modal synergistic anticancer effects. This work may shed some light on the development of novel multi-modal cancer therapies without any external intervention.